The investigation of classroom communication strategies used by English department lecturers - Putri Mareza; Sofyan A. Gani; Iskandar Abdul Samad (Universitas Syiah Kuala, 2021)
This case study is aimed at finding out the types of classroom communication strategies employed by English department lecturers during their teaching. In this study, three lecturers participated (HQ, RR, and SW in pseudonyms). They were lecturers for academic English, critical speaking, and advanced reading classes. The instruments of this study were videotapes, observation guides, field notes, and interview guides. After the data collection process, the data were analyzed using coding analysis and interactive analysis. The results showed that the most employed direct strategies were circumlocution and code-switching. HQ used circumlocution 54 times and code-switching 51 times; RR used circumlocution 21 times and code-switching 32 times. The major use of indirect strategies was comprehension check, which was used 47 times by RR, 28 times by HQ, and 9 times by SW. Last, for the interactional strategy, filler was the most used strategy. RR used it 19 times, HQ used it 46 times, and SW used it 26 times. It is suggested that lecturers are expected to balance these three strategies to maintain good teacher-student communication. However, for adult learners (college students), it is found that lecturers mostly use circumlocution during the lecture.